Dstyk mutation leads to congenital scoliosis-like vertebral malformations in zebrafish via dysregulated mTORC1/TFEB pathway - Xianding Sun (Nature Portfolio, 2020)
Congenital scoliosis is a complex genetic disorder characterized by vertebral malformation. Here, the authors demonstrate that loss of dstyk leads to scoliosis in zebrafish due to dysregulated biogenesis of notochord vacuoles and that DSTYK is required for lysosome biogenesis through mTORC1 regulation.